Development and Validation of a Short Food Frequency Questionnaire (SH-FFQ) in Iranian Adults: A Prospective Longitudinal Study - Sakineh N. Saeidlou; Parvin Ayremlou; Mohammad Alizadeh (International Journal of Preventive Medicine)
Background: An accurate assessment of food intake is necessary to monitor nutritional status. However, differences in cultures and dietary habits between communities make it necessary to create culturally specific tools to evaluate food intake. This study aimed to develop and validate a short food frequency questionnaire (SH-FFQ) in Iranian adults. Methods: This perspective longitudinal study was conducted during four months. A total of 135 healthy adults over 18 years (both of sex) were included. The 24-hour dietary recalls (24-HDRs) (three times per month: A total of 12 numbers) were collected as reference for validation of SH-FFQ. Participants completed two SH-FFQ, once at the end of the fourth month for validity, and the second one week after the first administration for reliability assessing. Results: Reliability analysis showed that the mean difference between the two SH-FFQs was not statistically significant (P > 0.05). None of the correlation coefficients (rs) were less than 0.4. There was a substantial or perfect correlation (r > 0.6) in 85.1% and a moderate correlation (r = 0.4–0.6) in 14.9% of food items. For validity assessment, the average values of two SH-FFQ1 and SH-FFQ2 (SH-FFQ) were compared with the average values of 24-HDRs. All of the intraclass correlation coefficients (ICCs) of between SH-FFQ and 24-HDRs were equal to or greater than 0.4 (except one item). Moderate correlation (ICC = 0.4–0.6) and substantial or perfect correlation (ICC > 0.6) were observed in 38.3% and 59.6% of food items, respectively. Conclusions: The current study showed that the developed SH-FFQ is reliable and valid in Iranian adults. This developed SH-FFQ can be used in nutritional assessments.